Portal Hypertension Recent Advances - Qi, Xingshun (IntechOpen, 2021)
Portal Hypertension - Recent Advances discusses several important topics related to portal hypertension, such as pediatric portal hypertension, sinusoidal obstructions syndrome, endoscopy in the management of portal hypertension, and non-invasive assessment of esophageal varices, along with recent advances in the field.